Talent management, absorptive capacity, and firm performance: Does it work in China and Russia?. Issue 5 (6th July 2018) - Latukha, Marina; Veselova, Anna
Abstract : This article investigates the relationship between talent management (TM), absorptive capacity (AC), and firm performance. We build a theoretical framework and examine the mediating role of a firm's AC in TM–performance relationships in the contexts of China and Russia. We use a sample of 120 Chinese and Russian firms to provide empirical evidence of our hypotheses. Our results show for both Chinese and Russian firms, a well‐developed TM system positively influences a firm's ability to acquire, assimilate, and exploit knowledge as well as increase the overall level of a firm's AC. We also found support for the argument that TM has an indirect positive effect on firm performance through its AC; moreover, the effect is stronger for Chinese firms, specifically, within the link between AC and performance.